PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR KIMIA SISWA KELAS X IPA PADA MATERI POKOK LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Ayustiani, Ayustiani; Haetami, Aceng; Tewa, Yuniati (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2021)
This study aims to determine: (1) Description of students' chemistry learning outcomes on electrolyte and non-electrolyte solution materials taught using the Problem Based Learning (PBL) model and by using the direct learning model; and (2) increasing student learning outcomes (N-gain) on electrolyte and nonelectrolyte solution materials taught using the Problem Based Learning (PBL) model and by using the direct learning model. The method used in this study was a quasi-experimental design using a pretest-posttest control group design. The sample in this study were students of class X IPA1 as the experimental class who were treated using the Problem Based Learning learning model and class X IPA2 as the control class treated with the direct learning model. Based on the results of the analysis, it was found that the data were: (1) Description of Chemistry learning outcomes of students who were taught using the application of the Problem Based Learning (PBL) model obtained an average value of 63.64 for the pre-test and 76.46 for the post-test. Meanwhile, the learning outcomes of students who were taught with the direct learning model had an average pre-test of 54.43 and an average post-test score of 61.57; (2) The increase in student learning outcomes after learning using Problem Based Learning (PBL) of 0.35 (medium category) is greater than the increase in student learning outcomes in learning using the direct learning model of 0.15 (low category). This indicates that the Problem Based Learning (PBL) learning model is applied effectively to students' chemistry learning outcomes.